KCNQ2 mutations: genotype-phenotype association beyond epilepsy. (3rd June 2015) - Buerki, SE; Horwath, GA; Van Allen, MI; Datta, A; Boelman, C; Abu Sharar, Z; Sayson, B; Connolly, MB; van Karnebeek, CD; Demos, MK
Abstract : Background: KCNQ2 abnormalities were described in infants with benign familial neonatal seizures (BFNS) and epileptic encephalopathy (EE). Associated features possibly include abnormal neuroimaging findings such as hypomyelination and/or T2 high signal of basal ganglia. Methods: This report describes 4 infants carrying different heterozygous KCNQ2 variants and 2 infants with 20q13.33 deletions encompassing KCNQ2 gene. Results: The different KCNQ2 mutations led to EE in 3 patients and included a novel de novo missense variant, p.Arg201Cys/c.601C>T, in an infant with severe EE and global developmental delay, hyperkinetic movement disorder, autonomic dysfunction with chronic hypoventilation, apnea, low GABA levels in CSF, and hypomyelination. She died at age 3 years of respiratory failure. One patient with BFNS and normal MRI has a previously reported c.508delG frame shift mutation in KCNQ2. Of the two de novo 22q13.33 deletions (1.2Mb versus 254.1 Kb) the larger caused a more severe phenotype, including focal epilepsy from infancy until 4 years, moderate developmental delay and diffuse brain volume loss. Conclusions: Along with varied epilepsy phenotypes and neuroimaging findings KCNQ abnormalities were associated with severe autonomic dysfunction and reduced CSF GABA levels. This might have further treatment implications, besides that the altered potassium channel function itself presents a therapeutic target.